2022
DOI: 10.1002/adfm.202206151
|View full text |Cite
|
Sign up to set email alerts
|

Air Induced Formation of Cs3Bi2Br9/Cs3BiBr6 Bulk Heterojunction and Its Dual‐band Photodetection Abilities for Light Communication

Abstract: Metal-halide perovskites have long carrier diffusion lengths, low trap densities, and high carrier mobilities, and are therefore of value in the development of photodetectors (PDs). However, the research on dual-band lead-free perovskite bulk heterojunction has not been well developed. Here, a novel air induced formation of Cs 3 Bi 2 Br 9 /Cs 3 BiBr 6 bulk heterojunction, reaching a high-performance dual-band photodetecting performance with an ultraviolet main band (360 nm) peak responsivity of 5.6 mA W −1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…A total of 1 μL of the solution was transferred to the center of the glass, which was covered by the target substrate. The growth temperature was maintained at 70 °C for 24 h. The detailed fabrication process is given in Figure b and our previous report …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 1 μL of the solution was transferred to the center of the glass, which was covered by the target substrate. The growth temperature was maintained at 70 °C for 24 h. The detailed fabrication process is given in Figure b and our previous report …”
Section: Methodsmentioning
confidence: 99%
“…The growth temperature was maintained at 70 °C for 24 h. The detailed fabrication process is given in Figure 1b and our previous report. 6 2.2. Characterization of MA 3 Bi 2 I 3x Br 9−3x (x = 0, 1, 2, and 3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Fang et al reported dual-band PDs by using Cs 3 Bi 2 Br 9 /Cs 3 BiBr 6 perovskite bulk heterojunction. [89] The device presented two spectral response peaks located at 360 and 450 nm, with responsivities of 59.4 and 3.09 mA W −1 , respectively. Remarkably, this device exhibited excellent optoelectronic performances in the UV band, including high detectivity of 1.2 × 10 12 Jones, a high on/off current ratio of 18 881, and a fast response speed (rise and fall times: 1.4 and 2 μs), respectively.…”
Section: Visible-uvmentioning
confidence: 97%
“…Nowadays, researchers have succeeded in synthesizing various 2D perovskite heterostructures such as (BA) [16]. Moreover, 2D OHP single-crystal heterostructures are of great importance for dual-band high-performance photodetectors due to the tunable optical bandgap allowing high absorption coefficients over multiple spectral regions [15,17]. It is of great importance to synthesize high-quality 2D OHP pure single crystals and their heterostructures instead of widely used polycrystalline films for higher detector performances [15].…”
Section: Introductionmentioning
confidence: 99%